5 years results impact data (ACP Secretariat BrusselsBE, 2018)
Presents the results of the 54 projects which have been compiled in a catalogue that provides insights into the impact, as well as the diversity of the activities carried out throughout the ACP states and regions, ranging from cheography to audiovisual production, music, 3D animation, architecture, literature and other artistic endeavours.
Keywords: ACP